PERAN IDOL K-POP DALAM MENDORONG TREN KONSUMEN: PERSPEKTIF GEOGRAFI REGIONAL - Nurhalimah; Syahrul Roji; Safa Regita Stiffany; Oot Hotimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Korean Wave (Hallyu) represents the globalization of culture that shapes cross-national consumption patterns, with K-pop as its central manifestation. This study aims to analyze the role of K-pop idols in driving consumer trends through a regional geography perspective. The research employed a qualitative descriptive approach using literature study by reviewing secondary sources such as journals, books, reports, and industry data. The findings reveal that K-pop idols function not only as entertainers but also as role models and brand ambassadors who influence consumption through fashion, cosmetics, and global brand collaborations. Regionally, consumption patterns vary: East Asia emphasizes physical consumption, North America highlights digitalization and hybridization, Europe prioritizes live concert experiences, while Southeast Asia demonstrates collective digital fandom contributing significantly to global streaming. These differences confirm the relevance of consumption geography theory in explaining spatial variations of popular culture. The study concludes that K-pop idols act as both cultural and economic agents shaping the consumer identity of the young generation. The limitation of this research lies in its reliance on secondary data; thus, future research is recommended to employ empirical methods such as surveys or interviews across regions to obtain deeper insights.